2014
DOI: 10.1371/journal.pone.0105242
|View full text |Cite
|
Sign up to set email alerts
|

Global Genetic Determinants of Mitochondrial DNA Copy Number

Abstract: Many human diseases including development of cancer is associated with depletion of mitochondrial DNA (mtDNA) content. These diseases are collectively described as mitochondrial DNA depletion syndrome (MDS). High similarity between yeast and human mitochondria allows genomic study of the budding yeast to be used to identify human disease genes. In this study, we systematically screened the pre-existing respiratory-deficient Saccharomyces cerevisiae yeast strains using fluorescent microscopy and identified 102 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Consistently, we found that 38 deletion mutants lacking genes required for mitochondrial protein synthesis failed to maintain a functional [ARG8 m ] genome -this is by far the largest group of genes required for this process. This is in good agreement with previous studies, which also reported that mitochondrial protein synthesis is particularly important for mtDNA maintenance [18,71]. Our results suggest that mitochondrial translation is required for mitochondrial genome maintenance even when respiratory activity is not required.…”
Section: Figure 3: Defining the Genes Required For Expression And Maisupporting
confidence: 94%
“…Consistently, we found that 38 deletion mutants lacking genes required for mitochondrial protein synthesis failed to maintain a functional [ARG8 m ] genome -this is by far the largest group of genes required for this process. This is in good agreement with previous studies, which also reported that mitochondrial protein synthesis is particularly important for mtDNA maintenance [18,71]. Our results suggest that mitochondrial translation is required for mitochondrial genome maintenance even when respiratory activity is not required.…”
Section: Figure 3: Defining the Genes Required For Expression And Maisupporting
confidence: 94%
“…A systematic analysis in yeast revealed 102 ORFs whose deletion led to the loss of mtDNA. Remarkably, 55% of those ORFs were associated with biosynthesis of mitochondrial proteins [32]. In humans, sex-specific quantitative trait loci for mtDNA content have been identified on chromosomes 1, 2 and 3 [33].…”
Section: Introductionmentioning
confidence: 99%
“…A low mtDNA content can be caused by mutations in the p53 gene, the POLG gene, and the gene for the mitochondrial transcription factor, TFAM [189, 338340]. In a yeast screen designed to identify nuclear genes involved in the maintenance of mtDNA, Zhang and Singh identified more than 50 human homologs whose inactivation caused depletion of mtDNA [414]. It is likely that germline variants or somatic mutations in these genes alter mtDNA content and may promote apoptotic resistance and risk of cancers.…”
Section: Disparities At the Mitochondrial Genome Level And Their Rmentioning
confidence: 99%